Encouraging Innovation: Thoughts from Ted Ames, Prize Winner - Silka, Linda (Maine Policy Review, 2014)
Competitions and prizes are being increasingly turned to as tools for stimulating innovation. Maine is fortunate to be home to Ted Ames, winner of a MacArthur “genius grant.” Ames continues to be a major force for finding innovative solutions to problems in Maine’s marine fisheries. In this interview with Linda Silka, he shares his thoughts and reflections not only on the impacts on innovation and of receiving this recognition, but also his understanding of the kinds of opportunities Maine needs to create for future generations if innovation is going to flourish.